Filtering to match hearing aid insertion gain to individual ear acoustics. - Bell SL (Trends in Amplification, 2009)
When hearing aid gain is prescribed by software, gain is calculated based on the average acoustics for the age of patient, gender, mold type, and so on. The acoustics of the individual's ear often vary from the average values, so there will be a mismatch between the prescribed gain and the real-ear gain. Real-ear measurement can be used to verify the gain and adjust it to meet targets, but the quality of the match will be limited by the number of channels and the flexibility of the hearing aid. A potential way to improve this process is to generate a filter that compensates for variations in real-ear insertion gain due to individual ear acoustics. Such a filter could be included in the processing path of a digital hearing aid. This article describes how such a filter can be generated using the windowing method, and the principle is demonstrated in a real ear. The approach requires communication between the real-ear measurement and hearing aid programming software. A finite impulse response filter with group delay just over 2 ms matched insertion gain to target values within the acceptable tolerance defined by British Society of Audiology guidelines.